Business Feasibility Analysis Based on Marketing Strategy in Printed Batik Imitation MSMEs (A Case Study of MEA Batik Pekalongan) - Daru Anggara Murty; Muhammad Naoval Haris; Saghira Nurul Adhifa (Jurnal Studi Manajemen dan Bisnis, 2026)
The development of digital marketing has encouraged Micro, Small, and Medium Enterprises (MSMEs) to utilize online platforms to enhance sales and business sustainability. However, the effectiveness of these strategies must be assessed alongside financial feasibility. This study aims to analyze the feasibility of a printed batik imitation MSME, MEA Batik Pekalongan, based on its digital marketing strategies through Shopee, TikTok, and Telegram. A quantitative descriptive approach was employed, supported by qualitative analysis through interviews, observations, and documentation of sales and production cost data. Financial feasibility was evaluated using Break Even Point (BEP), Payback Period (PP), and Benefit-Cost Ratio (B/C). The results show a monthly gross revenue of IDR 52,050,000 with a net profit of IDR 10,342,625. The BEP of 423 units per month is lower than actual sales of 875 units, while the Payback Period is achieved in approximately 2 months, with a B/C ratio of 1.29. Telegram yields the highest profit margin, while Shopee and TikTok expand market reach. Overall, multi-platform digital marketing integration improves profitability and indicates that the business is financially feasible for further development.